1975
DOI: 10.1152/ajplegacy.1975.228.6.1921
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and oncotic pressure measurements in inner medulla of mammalian kidney

Abstract: The vasa recta are thought to play an important role in the transfer of water andsolutes within the renal medulla. Hydraulic pressures were measured in vasa recta onthe surface of the exposed papilla in young Munich Wistar rats, and blood was collected from these microvessels for determination of total protein concentration and calculation of colloid oncotic pressure. In descending vasa recta at the base of the exposed papilla, mean hydraulic pressure was 9.2 plus or minus 0.4 (SE) mmHg and plasma protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Those experiments have been interpreted to demonstrate AVR uptake ofwater from the papillary interstitium. This is consistent with the need ofthe microcirculation to reabsorb water deposited by the loops of Henle and collecting tubule (22)(23)(24). Perfusion rates in these experiments were similar to blood flow rates in vivo and diffusion of albumin was found to be undetectable.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Those experiments have been interpreted to demonstrate AVR uptake ofwater from the papillary interstitium. This is consistent with the need ofthe microcirculation to reabsorb water deposited by the loops of Henle and collecting tubule (22)(23)(24). Perfusion rates in these experiments were similar to blood flow rates in vivo and diffusion of albumin was found to be undetectable.…”
supporting
confidence: 85%
“…In the hydropenic Munich-Wistar rat, under experimental conditions in which the ureter has been excised to access the papilla for micropuncture, it has been observed that plasma protein concentration falls during transit from papillary tip to base in the AVR (22)(23)(24). Those experiments have been interpreted to demonstrate AVR uptake ofwater from the papillary interstitium.…”
mentioning
confidence: 99%
“…The rats remained nondiuretic throughout the study as indicated by the mean ratios for urine-to-systemic plasma osmolality and urine-to-systemic plasma inulin. (21) and, in a later study (22), of VR at the papillary tip were slightly lower than 7 g/100 ml. In correcting the present data for plasma water we used the highest mean value.…”
Section: Resultsmentioning
confidence: 61%
“…Water is transported from the lumen of DVR to the papillary interstitium despite the fact that plasma oncotic pressure exceeds hydraulic pressure in the hydropenic Munich-Wistar rat. Sanjana et al recognized that a large negative pressure within the papillary interstitium could not explain this observation because water is transported from the papillary interstitium into ascending vasa recta (3,16,17). Based upon this analysis Experimental model.…”
Section: Discussionmentioning
confidence: 99%